(untitled) (Polis (Santiago), 2018)
The article presents some conclusions of the investigation about the representation of the Argentine State in the political discourse of social movement “Madres de la Plaza de Mayo” during 2001-2002. For such effect, a critical analysis of the discourse in order to identify how the discursive elements developed by this social movement during the foresaid period utilizes a set of discursive elements that limit or strengthen the meaning of the notion of State in Argentina, as well as it states the meaningful relations that this has for the democratic development of a country. This on the bases of the theoretical perspective worked by Joseph Courtés, Louis Panier and Jonathan Potter